THE THE ROLE OF TEACHERS IN IMPROVING STUDENT'S INTEREST IN LEARNING IN CLASS V OF CENING PIBLIC PRIMARY SCHOOL, CIKEDAL DISTRICT : THE ROLE OF TEACHERS IN IMPROVING STUDENTS' INTEREST IN LEARNING IN CLASS V OF CENING 2 PUBLIC PRIMARY SCHOOL, CIKEDAL DISTRICT - Rika Rika Zahrotul Wardah; Sulistia Dewi Angraeni; Enah Riyanti; Sofi Amalia; Dini Agustini; Yuniken Iranda; Ade Sofyan (Cakrawala Pedagogik, 2026)
The most fundamental aspect of a teacher's job is to fulfill his responsibilities to the school and his students. Developing pupils' interests is one of the teacher's responsibilities. Of course, teachers have a lot of options, like inspiring kids and getting to know them better. This is due to the fact that curiosity is a component of concentrating on something that is linked to emotions of fulfillment and pleasure. The purpose of this study is to ascertain the role that teachers play in helping grade V students at SD Negeri Cening 2 develop their interest as well as the challenges that these teachers must overcome. This study employs a disruptive research design and a qualitative methodology. Students, grade V homeroom instructors, and school principals served as the study's subjects. The findings demonstrated that the role of the teacher had a significant impact on the growth of students' interest, beginning with the procurement of programs and implementation of interest development in schools, understanding the types of student interest, and the teacher's attitude by motivating students and involving them in conventions so that interest is strong and students can contribute to the recognition of student achievement at school. Regarding the challenges educators confront in encouraging students' interest, there are still insufficient specialists in a variety of subject areas. Lack of proper infrastructure is another challenge that teachers frequently face.